Comparative Analysis of Use and Perceived Attributes of ICTs in Public and Private Extension Systems in India - Lakher, Raksha; Rao I, Sreenivas; Meera, Shaik N. (Journal of Agricultural Extension Management, 2019)
ICT enabled extension offers new opportunities for bridging the knowledgeand extension service gap in Indian agriculture. However, several criticalchallenges still remain. One of the most critical issues related to use of ICTs inthe extension system is perceived use of ICTs within these systems. A study wasconducted to know about sources of information, use of ICTs, and theperceived attributes of ICTs in private, public and other agricultural extensionorganizations. While planning to integrate ICTs into the extension system, it isimportant to consider perceived attributes of ICTs rather than the actualattributes. The results and discussions pertain to the perceived attributes ofICTs as technology per se. On the basis of these attributes, extensionorganizations may consider evolving ICT enabled extension strategies.